Treatment of pilonidal sinus by phenol injection. - Kelly, S. B. (Ulster Medical Society, 1989)
This report reviews the treatment of pilonidal sinus by phenol injection in 54 patients. Forty-four patients were treated initially by phenol injection and this was successful in 70%. The median number of injections per patient was one (range 1-5) with a median hospital stay per injection of two days (range 1-17 days). The median time to complete healing for patients treated by injection alone was two months (range 1-32 months). These results compare very favourably with more radical methods of treatment.